Pengembangan Indikator Kinerja Keselamatan Transportasi Jalan - Zulfikri, Zulfikri (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
Risk of an aaident will be e7.lf!11 greater in line 7lrith lncreaseri rienumd for transportation. The qualityof road accident infomuztion is needed for the guuenz111ent i11 order to impraue road sa.fett; performance.77re analyisis is carried bi; road transport safety benchmarking indicators that have beendevelaped and used bij ot!U?r countries so that tire level of road transport accidents can be detected andmeasured accurately and in accordance with international conventions. In that circumstances, measurementof road sa.fety performance in Indonesia, must be use minimum three indicators. All threeindicators are: 1) The number of aaidents or fatalities caused m; traffic aaidents/ total -population, 2)771£ number of accidents or fatalities caused by traffic accidents / 11ehicle population and 3) 77renumber of aaidents or fatalities caused m; traffic accidents / number of moues (vehicle - km).